The Role Of Msmes In Stimulating Local Economic Growth In Rantepao District, North Toraja Regency - Mustari Mustari; Nur Arisah (International Journal of Business and Quality Research, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a significant role in national and local economic growth. In Rantepao District, MSMEs play a crucial role not only in job creation and increasing community income, but also in preserving local culture and developing community-based tourism. This study employed a qualitative approach with a descriptive and exploratory design. Data were collected through in-depth interviews, participant observation, Focus Group Discussions (FGDs), and documentation studies. Informants were selected using purposive and snowball sampling techniques, consisting of MSME actors and related stakeholders. Analysis was conducted using thematic analysis methods. The results show that MSMEs in Rantepao play a strategic role in driving the local economy by absorbing labor, increasing income, and preserving regional culture. Internal factors such as self-efficacy and achievement motivation among MSME actors, especially the younger generation, are key to success. However, challenges such as limited access to capital, entrepreneurship training, and digital technology adoption remain major obstacles